2005
DOI: 10.1002/glia.20278
|View full text |Cite
|
Sign up to set email alerts
|

TLR3‐mediated signal induces proinflammatory cytokine and chemokine gene expression in astrocytes: Differential signaling mechanisms of TLR3‐induced IP‐10 and IL‐8 gene expression

Abstract: Viral infection is one of the leading causes of brain encephalitis and meningitis. Recently, it was reported that Toll-like receptor-3 (TLR3) induces a double-stranded RNA (dsRNA)-mediated inflammatory signal in the cells of the innate immune system, and studies suggested that dsRNA may induce inflammation in the central nervous system (CNS) by activating the CNS-resident glial cells. To explore further the connection between dsRNA and inflammation in the CNS, we have studied the effects of dsRNA stimulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 31 publications
9
121
1
Order By: Relevance
“…They further showed that pIC induced a marked bias toward genes known for their role in host defense against viruses. As expected, and in agreement with previously published data (4,17), pIC also induced a wide array of chemokines and cytokines characteristic of TLR activation.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…They further showed that pIC induced a marked bias toward genes known for their role in host defense against viruses. As expected, and in agreement with previously published data (4,17), pIC also induced a wide array of chemokines and cytokines characteristic of TLR activation.…”
Section: Resultssupporting
confidence: 93%
“…Using microarray technology, we found, in agreement with others (4,10,17), that pIC induced a wide range of cytokines and chemokines characteristic of an innate immune response, but we also noted a marked bias toward genes characterized for their role in antiviral responses when results were compared with similar data sets produced in response to the cytokine IL-1 (Table I). Cells were then stimulated with 10 g/ml pIC for 24 h, total cell homogenates were isolated and immunoblotted for viperin.…”
Section: Discussionsupporting
confidence: 90%
“…It is important to note that previous in vivo studies of the inflammatory response to CNS virus infection and chronic EAE have demonstrated that astrocytes are a major source of CXCL10 13, 31, 32. Our observations of CXCL10 production by DCs and T cells in an antigen‐specific in vitro system do not rule out the possible additional production of CXCL10 by astrocytes or other cells in patients with PND.…”
Section: Discussionmentioning
confidence: 99%
“…The intrastriatal administration of drugs was modified from a previously described method (Heneka et al, 2000;Park et al, 2006). Briefly, male C57BL/6 mice (approx.…”
Section: Animals and Stereotaxic Injectionmentioning
confidence: 99%
“…Brains were removed and postfixed at 4 o C overnight, transferred to 30% sucrose in PBS for 48 h, and then coronal sections (30 m thickness) were prepared on a cryostat. The immunohistochemical analysis of floating sections was performed as previously described (Park et al, 2006). Briefly, sections were incubated for 30 min with 3% H2O2 in 0.1 M PBS (pH 7.4), then blocked with a solution containing 5% normal goat/or horse serum, 2% BSA, 2% FBS, and 0.1% triton X-100 for 2 h at room temperature (RT).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%